Prevention and Treatment of Sarcopenia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sarcopenia represents the decline in skeletal muscle mass and function with age, characterized by the muscle fiber's quality, strength, muscle endurance, and metabolic ability decreasing, as well as the fat and connective tissue growing.Reduction of muscle strength with aging leads to loss of functional capacity, causing disability, mortality, and other adverse health outcomes. Because of the increase of the proportion of elderly in the population, sarcopenia-related morbidity will become an increasing area of health care resource utilization.Diagnostic screening consists of individuation of body composition, assessed by DEXA, anthropometry, bioelectrical impedance, MRI, or CT scan. Management is possible with resistance training exercise and vibration therapy, nutritional supplements, and pharmacological treatment.The book includes articles from different nationalities, treating the experimental and medical applications of sarcopenia. The consequences of sarcopenia in frailty are treated in relation to other associated pathologies or lesions, as femoral neck fractures and hepatocellular carcinoma.